Birthing black mothers - Nash, Jennifer Christine 1980- (Duke University Press, 2021)
"Jennifer C. Nash examines how the figure of the "Black mother" has become a powerful political category synonymous with crisis, showing how they are often rendered into one-dimensional symbols of tragic heroism and the ground zero of Black life."--
Keywords: African American mothers; Womanism; Black lives matter movement; Doulas / United States; Reproductive health services / Social aspects / United States; African American women / Medical care / United States; Race discrimination / Health aspects / United States; African American women / Medical care; Doulas; United States